Peran Guru Penjaskes dalam Meningkatkan Minat Belajar Siswa terhadap Pembelajaran PJOK - Eva Safitri; Meirizal Usra; Herri Yusfi (Jendela Olahraga, 2022)
This study aims to determine whether the use of learning videos using the google meet application during the Covid-19 pandemic can improve learning outcomes in the material of rhythmic motion activities in class V SDN 2 South Loktabat students. The method used in this research is classroom action research (classroom action research), with the model of Kemmis and Taggart (planning, implementing action, observing and reflecting. The subjects of the study were 27 students of class V-A SDN 2 South Loktabat. The data collection instruments were tests (multiple choice) and non-test (observation). Overall data in the form of quantitative data then analyzed descriptively using the percentage formula. The results of the study showed an increase in student learning outcomes from cycle one to cycle two. In the first cycle, the affective value was 67%, then in the second cycle increased by 93%, the cognitive value in the first cycle was 52%, then in the second cycle increased by 89%, the psychomotor score in the first cycle was 56% than in the second cycle is increased by 93%. It can be concluded that learning using google meet by utilizing instructional videos can improve learning outcomes of rhythmic gymnastics activities of class V students of SD Negeri 2 South Loktabat.